Emerson's life in science : the culture of truth - Walls, Laura Dassow (Cornell University Press, 2003)
"Ralph Waldo Emerson has traditionally been cast as a dreamer and a mystic, concerned with the ideals of transcendentalism rather than the realities of contemporary science and technology. In Laura Dassow Walls's view Emerson was a leader of the secular avant-garde in his day. He helped to establish science as the popular norm of truth in the United States and to modernize American popular thought. In addition, he became a hero to a post-Darwinian generation of Victorian Dissenters, exemplifying the strong connection between transcendentalism and later nineteenth-century science."